Innowacyjność jako kluczowy element konkurencyjności gospodarek Polski i Finlandii - Dobrzański, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Currently, some countries find it increasingly difficult to be competitive and to maintain good economic indicators. The main subject of the article is to present that the innovation is one of the key elements affecting international competitiveness. For this purpose competitiveness and innovation are defined, and the relationship between them is presented. The paper also discusses the innovative policy of two countries: Finland and Poland. This analysis allowed to compare two extreme economies, indicate main causes of these differences and draw conclusions for Poland.
Keywords: innowacyjność; konkurencyjność; gospodarka; Polska; Finlandia